Pengaruh Kadar Perekat Urea Formaldehida Terhadap Kualitas Papan Partikel dari Kayu Gamal (Gliricidia sepium - Jonyal Periandi Sitanggang; Tito Sucipto; Irawati Azhar (Program studi Kehutanan USU, 2015)
The stalk of the gamal wood is one of potential raw material for manufacturing particleboard. The purpose of this study was to evaluate the effect of urea formaldehyde adhesives content on physical and mechanichal properties of the particleboard and to determine the optimum urea formaldehyde adhesives content for the gamal particleboard. Particleboard were made with size 25 cm x 25 cm x 1 cm with density of 0,8 g/cm3. The particleboard be pressed by 1200C temperature during 8 minute with pressure 25 kg/cm2. Result showed the treatment of adhesive content have significant influence on moisture content, water absorption, thickness swelling, modulus of rupture (MOR) and internal bond (IB) gamal particleboard. The optimum treatment of urea formaldehyde adhesive content is 11%.Key words: Gliricidia sepium, particleboard, adhesive content, quality